Enti ecclesiastici cattolici e procedure concorsuali. La rilevanza del “patrimonio stabile” nella gestione della crisi (Stato, Chiese e pluralismo confessionale, 2015)
Contributo sottoposto a valutazioneSOMMARIO: 1. Premessa - 2. Le attività degli enti ecclesiastici. - 3. Il problema dell’applicabilità delle procedure concorsuali - 4. L’evoluzione della giurisprudenza domestica - 5. Il patrimonio stabile tra dato normativo e realtà giuridica - 6. Termini e garanzie di trasparenza dell’utilizzo del concetto di “patrimonio stabile”: i controlli canonici nell’ordinamento italiano - 7. Riflessioni conclusive. Abstract: Ecclesiastical institutions in financial crisis. The role of “stable patrimony”Within the economic framework coming from the 2008 financial downturn, many ecclesiastical institutions involved in commercial activities found themselves in severe financial crises, sometimes leading them to not be able to reimburse their debts. The enforcement of a classical bankruptcy law however does not seem to be fully tailored on these ecclesiastical institutions specificities. Indeed the current Italian bankruptcy law puts the ecclesiastical institutions assets under an indiscriminate attack that can seriously affect their survival and thus to ensure the satisfaction of the "religious" needs they exist for.In such a context, given the statement of the article 7.3, Law 121/1985 which emphasizes that the common law should be applied paying particular attention to the structure and the purpose of religious institutions, the present work attempt at developing a fist reflection on a specific canon law regulatory scheme, i.e. the "stable patrimony", which aim is to guarantee and protect a minimum assets useful to the survival of the ecclesiastical organization. After a first description and analysis of the "stable patrimony" profiles in a canon law perspective, the issue will be also addressed from the relevant point of view of the Church and State relations treaties.